Pengaruh Media Pembelajaran Infografis Berbasis Aplikasi Android Terhadap Tingkat Pengetahuan Mengenai Obesitas Pada Remaja Putri - Yoswenita Susindra; Riasyah Al Waja Permatasari (Puslitbang Sinergis Asa Professional, 2023)
Obesity is still an epidemic health problem worldwide. Obesity is a condition in which a person is overweight due to abnormal fat tissue deposits. The cause of obesity is a diet that has been consumed in excess of the need for unbalanced nutrients. Obesity is also caused by various factors related to changes in one's lifestyle that lead to a sedentary lifestyle. The level of knowledge about obesity is one of the factors that influence the formation of an attitude in preventing overweight and obesity. The purpose of this study was to determine the effect of infographic media based on android applications regarding obesity on knowledge of obesity in young women. This research is a quantitative study using a pre-experimental design method with a one group pre- test post-test design. The number of subjects in this study were 74 female students using the simple random sampling technique. The results showed that female adolescents experienced an increase in knowledge from 84.27 to 99.03 after being given an android application media intervention regarding obesity. This proves the influence of the android application regarding obesity on knowledge in young women, with a p-value = 0.000 <0.05.